Practical Rubber Rheology and Dynamic Properties - Dick, John S. (Carl Hanser Verlag, 2023)
Practical Rubber Rheology and Dynamic Properties provides a unique overview of rubber rheology from a practical perspective. Targeted at rubber practitioners in the rubber industry, it focuses largely on applications of rubber rheology testing to solving industrial problems, rubber compound development, predicting changes in processability in the plant, quality assurance, and research and development. However, basic principles are covered as well.